National security of Bangladesh in the twenty first century - Kabir, Mohammad Humayun (Dhaka : Academic Press, 2000)
Contributed articles presented at a national seminar held on 29-30 Nov. 1998 organized by BIISS in Dhaka.
Includes bibliographical references.
Keywords: National security -- Bangladesh